2023
DOI: 10.1063/5.0134353
|View full text |Cite
|
Sign up to set email alerts
|

Non-negligible roles of charge transfer excitons in ultrafast excitation energy transfer dynamics of a double-walled carbon nanotube

Abstract: Herein, we employed a developed LR-TDDFT-based nonadiabatic dynamics simulation method that explicitly takes into account the excitonic effects to investigate photoinduced excitation energy transfer dynamics of a double-walled CNT model with different excitation energies. The low E11 excitation of the outer CNT that generates a locally excited (LE) |out*⟩ exciton does not induce any charge separation. In contrast, the E11 excitation of the inner CNT can generate four kinds of excitons with the LE exciton |out*… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 141 publications
1
19
0
Order By: Relevance
“…Recently, we extended the LR-TDDFT-based NAMD simulation method, which is mainly used for investigating molecular systems, to semiconductor materials as well to incorporate the excitonic effects in periodic systems. 116 The developed method was used to evaluate the photoinduced excitation energy transfer dynamics of a doublewalled CNT (DWCNT) model composed of SWCNT(11,0) (inner CNT) and SWCNT(20,0) (outer CNT) with different excitation energies. Our simulation results indicated that the DWCNT may exhibit different exciton dynamics upon excitation with different energies and the CT and dark excitons are expected to play important roles during the whole process (Figure 14).…”
Section: Dwcnt and Excitonic Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we extended the LR-TDDFT-based NAMD simulation method, which is mainly used for investigating molecular systems, to semiconductor materials as well to incorporate the excitonic effects in periodic systems. 116 The developed method was used to evaluate the photoinduced excitation energy transfer dynamics of a doublewalled CNT (DWCNT) model composed of SWCNT(11,0) (inner CNT) and SWCNT(20,0) (outer CNT) with different excitation energies. Our simulation results indicated that the DWCNT may exhibit different exciton dynamics upon excitation with different energies and the CT and dark excitons are expected to play important roles during the whole process (Figure 14).…”
Section: Dwcnt and Excitonic Effectsmentioning
confidence: 99%
“…Lu et al combined the LR-TDDFT method with NAMD method to investigate the excitonic effects on the ultrafast charge separation and energy transfer process in TMD heterojunctions. , It is worth emphasizing that in order to reduce the computational effort associated with the Fock-like exchange on large systems, they applied first order perturbation theory to the range-separated hybrid Kohn–Sham Hamiltonian and obtained the first-order corrected eigenvalues and eigenfunctions. Recently, we extended the LR-TDDFT-based NAMD simulation method, which is mainly used for investigating molecular systems, to semiconductor materials as well to incorporate the excitonic effects in periodic systems . The developed method was used to evaluate the photoinduced excitation energy transfer dynamics of a double-walled CNT (DWCNT) model composed of SWCNT­(11,0) (inner CNT) and SWCNT­(20,0) (outer CNT) with different excitation energies.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aiming to explore detailed interlayer hole transfer processes from the MoSe 2 to the WSe 2 upon the photoexcitation, a set of NAMD simulations accompanied with the “neglect of back-reaction” approximation (also known as the “classical path approximation”), powerful tools for revealing ultrafast dynamics of the photoreaction, , charge transfer, charge recombination, and charge transport upon photoexcitation in molecular and periodic systems, are conducted for H 0L , H 1L , H 2L , and H 3L configurations at a temperature of 100 K (denoted as H 0L -100K, H 1L -100K, H 2L -100K, and H 3L -100K, respectively). Besides, the temperature effect has been examined by performing another simulation for H 3L at a temperature of 300 K (H 3L -300K) (Figure ) (details are listed in Supporting Information).…”
mentioning
confidence: 99%
“…This approach is based on the following three considerations. First, the inclusion of the excitonic effect requires the GW Bethe–Salpeter equation (GW-BSE) or the time-dependent DFT (TDDFT) ,, to describe the many-body effect, requiring too expensive and unaffordable computation resources for NAMD simulations. Second, previous investigations have proved that NAMD simulations within the DFT framework could provide useful results for the type-II heterostructures where only the electron transfer or the hole transfer is considered the major process upon the photoexcitation .…”
mentioning
confidence: 99%